Evaluation of the urban living lab in HEIs towards education for sustainable development (E-ULL-HEIs) - Morales, Ivetheyamel; Segalás, Jordi; Masseck, Torsten (Frontiers in Education, 2024)
This study explores the implementation of Urban Living Labs (ULLs) in Higher Education Institutions (HEIs) to promote Education for Sustainable Development (ESD). It adopts a methodology that integrates a mixed approach, combining literature review, validation with experts in the field and analysis of case studies. A structured evaluation tool is proposed based on three constructs: Synergy, Strategy and Pedagogy, which cover the essential characteristics of the three thematic axes: ULLs, ESD and HEIs, through seven indicators. This tool is applied to examine the effective-ness of ULLs in promoting sustainable practices within the university context. The results, vali-dated through experts, exploratory factor analysis and Cronbach's alpha coefficient, demonstrate the reliability and consistency of the evaluative indicators, highlighting the crucial role of ULLs in the integration of sustainability in the curriculum, experiential learning, and the impact social and community. This approach allowed the identification of successful practices and common challenges in the implementation of ULL, as well as the development of a framework of indicators adapted to the specific needs of HEIs. The study concludes by emphasizing the transformative potential of ULLs in HEIs to advance towards sustainable urban transitions, underscoring the need for robust evaluative tools to optimize the contribution of higher education to global sustainable development.